TMA NEWS: 18-FEB-2002 (20020218) WORLD. (1) NEW YORK: TAXPAYER GROUP APPLAUDS BLOOMERG'S SPENDING RESTRAINT WHILE WARNING AGAINST REGRESSIVE TAX INCREASE (Tufts Archival Research Center, 2007)
Document containing many articles published on the tobacco industry. Contains articles regarding taxes, secondhand smoke and legislation among many others. Categorizes the articles with keywords. Includes the title of the article as well as the author, the day it was published and in what periodical.